IoT-Enhanced mechanical system for fogponic cultivation: Air circulation and environmental control - Heltha, Fahri; Yunidar, Yunidar; Syahyadi, Rizal; Melinda, Melinda; Azhari, Rizki; Elizar, Elizar (Jurnal Polimesin, 2025)
Fogponic cultivation, a hydroponic technique that utilizes water mist for nutrient delivery, offers a significant advantage in water and nutrient efficiency. However, suboptimal air circulation, temperature, and humidity in the root chamber can hinder plant growth and nutrient uptake. This study develops an IoT-enhanced mechanical system to optimize environmental conditions in a fogponic root chamber for cultivating spinach (Spinacia oleracea) seedlings. An actuator in the form of a fan was integrated to regulate air circulation, and managed by a Proportional Integral Derivative (PID) controller for precise temperature and humidity control. The system was monitored using the IoT-based Blink application. The results showed that the PID controller effectively regulated environmental conditions, with optimized parameter values: Kp = 5.76, Ki = 0.576, and Kd =14.4. Performance comparisons with P, PI, and PD controllers demonstrated effective humidity control, achieving the target set point of 92% with rise times of 447–1090 seconds and steady-state errors of 0–0.5%. By integrating mechanical components such as the fan with IoT-based monitoring, the system achieves continuous adjustments to the environment, enhancing plant growth conditions.